Profiles of Amino Acids and Acylcarnitines Related with Insecticide Exposure in Culex quinquefasciatus (Say) - Guedes, Raul Narciso Carvalho; Martin Park, Abdiel; Gómez Govea, Mayra Alejandra; López Monroy, Beatriz; Treviño Alvarado, Víctor Manuel; Torres Sepúlveda, María del Rosario; López Uriarte, Graciela Areli; Villanueva Segura, Olga Karina; Ruiz Herrera, María del Consuelo; Martínez Fierro, Margarita de la Luz; Delgado Enciso, Iván; Flores Suárez, Adriana Elizabeth; et al. (2017)
Culex quinquefasciatus Say is a vector of many pathogens of humans, and both domestic and wild animals. Personal protection, reduction of larval habitats, and chemical control are the best ways to reduce mosquito bites and, therefore, the transmission of mosquito-borne pathogens. Currently, to reduce the risk of transmission, the pyrethroids, and other insecticide groups have been extensively used to control both larvae and adult mosquitoes. In this context, amino acids and acylcarnitines have never been associated with insecticide exposure and or insecticide resistance. It has been suggested that changes in acylcarnitines and amino acids profiles could be a powerful diagnostic tool for metabolic alterations. Monitoring these changes could help to better understand the mechanisms involved in insecticide resistance, complementing the strategies for managing this phenomenon in the integrated resistance management. The purpose of the study was to determine the amino acids and acylcarnitines profiles in larvae of Cx. quinquefasciatus after the exposure to different insecticides. Bioassays were performed on Cx. quinquefasciatus larvae exposed to the diagnostic doses (DD) of the insecticides chlorpyrifos (0.001 μg/mL), temephos (0.002 μg/mL) and permethrin (0.01 μg/mL). In each sample, we analyzed the profile of 12 amino acids and 31 acylcarnitines by LC-MS/MS. A t-test was used to determine statistically significant differences between groups and corrections of q-values. Results indicates three changes, the amino acids arginine (ARG), free carnitine (C0) and acetyl-carnitine (C2) that could be involved in energy production and insecticide detoxification. We confirmed that concentrations of amino acids and acylcarnitines in Cx. quinquefasciatus vary with respect to different insecticides. The information generated contributes to understand the possible mechanisms and metabolic changes occurring during insecticide exposure.